THE INFLUENCE OF TOURISM SECTOR AND TRADE ON ECONOMIC GROWTH IN INDONESIA - Sipahutar, Tetty Tiurma Uli (Universitas Negeri Medan, 2019)
The results showed some conclusions: (i) in the long term that the variables of tourism foreign exchange and net exports positive and significant impact. Dummy variables and the exchange rate and no significant positive effect. (ii) in the short term that the variables of tourism foreign exchange and net exports positive and significant impact. And a dummy variable exchange rate and no significant positive effect. (iii) of the coefficient of determination (R2) showed that the variables studied could explain the long-term and short-term equal to 94.01 percent, while the remaining 5.99 percent is explained by variables out of models (which was not studied).